Chronic nonbacterial osteomyelitis: the role of whole-body MRI - Marcelo Astolfi Caetano Nico; Flávia Ferreira Araújo; Júlio Brandão Guimarães; Isabela Azevedo Nicodemos da Cruz; Flávio Duarte Silva; Bruno Cerretti Carneiro; Alípio Gomes Ormond Filho (Insights into Imaging, 2022)
Abstract Background Chronic nonbacterial osteomyelitis (CNO), also known as chronic recurrent multifocal osteomyelitis, is a noninfectious autoinflammatory disorder that occurs primarily in children and adolescents and is characterized by episodic musculoskeletal pain with a protracted course. Main body Traditionally, the diagnosis of CNO is made by exclusion and commonly requires bone biopsy to rule out infection and malignancy. However, bone biopsy may be avoided when imaging and clinical characteristic features are present, such as multifocal bone lesions at typical sites, no constitutional symptoms and no signs of infection in laboratory test results. Whole-body magnetic resonance imaging (WB-MRI) can assess signs of acute and chronic inflammation and enables the detection of CNO typical patterns of lesion location and distribution, thereby helping to exclude differential diagnosis. The goal of the present study paper is to review the main clinical and imaging aspects of the disease with emphasis on the role of WB-MRI in the diagnosis, assessment of disease burden and follow-up monitoring. Conclusion Radiologists need to be familiar with the imaging features to suggest the diagnosis as the early therapy may help to avoid irreversible secondary damage of skeletal system.